Komunikasi Organisasi dan Perannya - Ansori .; Sri hartini; Eka Novitasari; Wahyuni . (CV. ITTC INDONESIA, 2026)
This study aims to analyze the role of organizational communication in improving the effectiveness of educational institutions. Organizational communication is understood as the process of information exchange, coordination, and interaction among organizational members, which serves to support the optimal achievement of educational goals. This study employed a library research method with a qualitative descriptive approach through analysis of various books, national journals, and relevant previous research findings from the past 10 years. The results indicate that organizational communication plays a crucial role in improving the effectiveness of educational institutions through clarity of information, strengthening work coordination, and creating a conducive work environment. Effective communication also influences teacher performance, learning quality, work motivation, and faster and more accurate decision-making. Furthermore, vertical, horizontal, and diagonal communication patterns are crucial factors in facilitating the flow of information within the school environment. Therefore, effective and structured organizational communication is key to creating professional, adaptive educational institutions capable of continuously improving the quality of education.